ANALYSIS OF INDONESIA'S COAL EXPORT COMPETITIVENESS IN THE INTERNATIONAL MARKET AND ITS DETERMINANT FACTORS - Dwiki Andreansyah Nugraha; Riko Setya Wijaya; Putra Perdana (Nurul Jadid University, 2025)
Indonesia is one of the world’s largest coal exporters, with a significant contribution tomeeting global energy demand. However, the competitiveness of Indonesia’s coalexports is strongly influenced by international market dynamics and external factors.This study aims to analyze the competitiveness of Indonesia’s coal exports in theglobal market using the Vector Autoregression (VAR) model for the period 2004–2023.The variables analyzed include Foreign Direct Investment (FDI), international coalprices (HBI), exchange rate (NT), national coal production, and competitivenessmeasured through the Revealed Comparative Advantage (RCA). The results indicatethat Indonesia still lags behind Australia in terms of RCA, although the gap hasnarrowed between 2018 and 2023. Conversely, compared to Russia, Indonesiaconsistently outperforms. The impulse response function (IRF) analysis reveals thatFDI has a positive impact on RCA, while rising international coal prices tend toweaken competitiveness. National coal production shows a positive effect in themedium term, whereas the exchange rate responds negatively to price fluctuations.Variance decomposition (VD) results show that FDI had a dominant contribution inthe early period (70–75%) but declined to around 20%, while the influence ofinternational coal prices increased to 40%. Overall, Indonesia’s coal exportcompetitiveness is largely shaped by external factors, requiring strategies such asmarket diversification, downstream industry development, efficiency improvements,and the optimization of global geopolitical opportunities.